Cardiovascular Disease in Primary Sjögren’s Syndrome: Raising Clinicians’ Awareness - Casian, Mihnea; Jurcut, Ciprian; Dima, Alina; Mihai, Ancuta; Stanciu, Silviu; Jurcut, Ruxandra (Frontiers in Immunology, 2022)
In the ever evolving landscape of systemic immune mediated diseases, an increased awareness regarding the associated cardiovascular system impairment has been noted in recent years. Even though primary Sjögren’s Syndrome (pSS) is one of the most frequent autoimmune diseases affecting middle-aged individuals, the cardiovascular profile of this specific population is far less studied, at least compared to other autoimmune diseases. Traditional cardiovascular risk factors and disease specific risk factors are inextricably intertwined in this particular case. Therefore, the cardiovascular risk profile in pSS is a multifaceted issue, sometimes difficult to assess. Furthermore, in the era of multimodality imaging, the diagnosis of subclinical myocardial and vascular damage is possible, with recent data pointing that the prevalence of such involvement is higher in pSS than in the general population. Nevertheless, when approaching patients with pSS in terms of cardiovascular diseases, clinicians are often faced with the difficult task of translating data from the literature into their everyday practice. The present review aims to synthesize the existing evidence on pSS associated cardiovascular changes in a clinically relevant manner.